Spanish seamen: classification of employments: statistical information
C01-0028-001 SPANISH SEAMEN. CLASSIFICATION OF EMPLOYMENTS. Mercantile Marine: Industry: Captain 15 General worker 13 (2 good English) Adjustor 12 1st Engineer 11 Assistant adjustor 6 2nd Engineer 2 Apprentice adjustor 2 Engineer 9 Mechanic 6 Engineer, Assistant mechanic 3 fishing boat 1 Mason 1 2nd Engineer, Book-keeper 4 fishing boat 2 Carpenter 3 Appr. Engineer 1 Cabinetmaker 1 Officer 11 Chauffeur 2 (1 perfect English) Chauffeur-mechanic 2 (1 good English) Watchmaker 2 Pilot 2 Electrician 1 Bo'sun 2 Electrical Assistant 2 Boilerman 4 Engineer 1 Greaser 5 Motor body worker 1 Stoker 25 Tractor mechanic 1 Cook 12 Mechanical saw operator 2 Seaman 17 Plumber 1 Steward 8 Dockyard worker 1 Baker Sheet metal worker 1 Butcher 2 Butcher 2 Deck hand 7 Railway metal worker 1 Carpenter 2 Furnace foreman 1 Mechanic Assist. eng. & surv. 1 (Diesel) 2 (10 yrs. Bilbao Town C.) Galleyboy 3 Female nurse (qual.) 1 (10 yrs.' exp Agriculture: General 43 Stock farm work 7 Anything: 5 captains, 1 officer, 1 2nd engineer, 9 seamen, 5 stokers, 2 cooks, 1 boilerman, 1 galleyboy, 1 cadet. AC 292C/946/1/28(i)